Examination of Teacher Competence and Leadership Levels of Physical Education Teachers - ÜNALDI, Gamze; SAYIN TEMUR, Canan (International Journal of Holistic Health, Sports and Recreation, 2023)
The aim of the study is to examine the teacher competence and leadership levels of physical education teachers. The sample of the study, in which the Descriptive Research model was used, included 417 teachers in the Black Sea region. Personal information form, Teacher Efficacy Scale and Teacher Leader ship Scale were used to collect the data of the study. The analysis of the data of our study, which was obtained through Google forms, was made with SPSS 22.0 software. Paired Sample t test was used to compare the scores obtained from the data showing normal distribution according to the skewness and kurtosis values, Pearson Correlation test to determine the relationship between the variables, Independent sample t test in binary variable groups, One Way ANOVA analysis was used for the comparison of multiple groups. In general, in line with the findings obtained in our study, it was determined that there is a significant positive difference between the level of proficiency of physical education teachers according to gender, the status of the graduated program, and leadership expectation and perception levels. It can be thought that awareness will be created in the literature with studies to be carried out with different disciplines in the field of sports sciences, such as this study conducted specifically for physical education teaching.